Внутривидовая изменчивость у некоторых видов Clausiliidae (Gastropoda, Pulmonata) под влиянием условий обитания - Байдашников, А.А. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Анализируется влияние биотопического (спектра основных биотопов) и территориального (распространение разных лесов по территории Украины) факторов на изменчивость количества оборотов, высоты раковины, величины высота/ширина раковины и количества ребер в 1 мм предпоследнего оборота у самых распространенных на территории Украины и части Молдовы видов Clausiliidae — Cochlodina orthostoma (Menke, 1830), Cochlodina laminata (Montagu, 1803), Ruthenica filograna (Rossmassler, 1836), Macrogastra latestriata (A. Schmidt, 1857), Laciniaria plicata (Draparnaud, 1801) и Bulgarica cana (Held, 1836). The species of Clausiliidae (Cochlodina orthostoma (Menke, 1830), Cochlodina laminata (Montagu, 1803), Ruthenica filograna (Rossmassler, 1836), Macrogastra latestriata (A. Schmidt, 1857), Laciniaria plicata (Draparnaud, 1801), Bulgarica cana (Held, 1836) are most widespread in Ukraine and a part of Moldova. The variability of shell parameters (the whorl number of shell, the shell height, the index of shell height/shell width, the rib number per 1 mm of the next to last whorl) was discussed. The variability of the parameters under influence of the biotopic factor (spectrum of main biotopes) and territorial factor (distribution of different forests on territory of Ukraine) are analyzed.